A Fibromatosis Case Mimicking Abdominal Aorta Aneurysm - Arzu Tasdemir; Cemal Kahraman; Kutay Tasdemir; Ertugrul Mavili (Case Reports in Cardiology)
Retroperitoneal fibrosis is a rare fibrosing reactive process that may be confused with mesenteric fibromatosis. Abdominal aorta aneurysm is rare too and mostly develops secondary to Behcet’s disease, trauma, and infection or connective tissue diseases. Incidence of aneurysms occurring as a result of atherosclerotic changes increases in postmenopausal period. Diagnosis can be established with arteriography, tomography, or magnetic resonance imaging associated with clinical findings. Tumors and cysts should be considered in differential diagnosis. Abdominal ultrasound and contrast-enhanced computerized tomography revealed an infrarenal abdominal aorta aneurysm in a 41-year-old woman, but, on surgery, retroperitoneal fibrosis surrounding the aorta was detected. We present this interesting case because retroperitoneal fibrosis encircling the abdominal aorta can mimic abdominal aorta aneurysm radiologically.